2018
DOI: 10.3390/app8081391
|View full text |Cite
|
Sign up to set email alerts
|

Low-Field NMR and MRI to Analyze the Effect of Edible Coating Incorporated with MAP on Qualities of Half-Smooth Tongue Sole (Cynoglossus Semilaevis Günther) Fillets during Refrigerated Storage

Abstract: Featured Application: The monitoring of quality characteristics of Half-smooth tongue sole (HTS, Cynoglossus semilaevis Günther) is essential during refrigerated period based on the edible coating incorporated with MAP treatment, which has not displayed in the previous literatures. Meanwhile, the low-field nuclear magnetic resonance (LF-NMR) and magnetic resonance imaging (MRI) technology has a potential development to assess the quality of aquatic products, which is applied to assess the water distribution an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…An amount of malonaldehyde (MDA) was employed to measure the extent of lipid oxidation [23,36]. Figure 4 showed that the MDA values for all samples increased during frozen storage, which agreed with the results of Xuan et al [30].…”
Section: Lipid Oxidationanalysissupporting
confidence: 85%
See 3 more Smart Citations
“…An amount of malonaldehyde (MDA) was employed to measure the extent of lipid oxidation [23,36]. Figure 4 showed that the MDA values for all samples increased during frozen storage, which agreed with the results of Xuan et al [30].…”
Section: Lipid Oxidationanalysissupporting
confidence: 85%
“…In addition, P23 corresponds to content of free water extramyofibrillar space. It was noted that there were no regular trends in P22 of all samples, while P23 of glazing samples first declined rapidly and then increased steadily [23]. Furthermore, the samples glazed with sodium polyacrylate and D-sodium erythorbate (SG-1DSE, SG-3DSE and SG-5DSE) had lower (p < 0.05) P23 than other groups (CK, WG and WG-DSE).…”
Section: Low Field-nuclear Magnetic Resonance (Lf-nmr) Analysismentioning
confidence: 93%
See 2 more Smart Citations
“…according to the method of Li et al [26]. Portions of 0.5 × 0.5 × 0.2 cm (about 1 g) were cut from the dorsal part of crayfish and sealed with polyethylene films.…”
Section: Lf Nmr Analysis Lf Nmr Analysis Was Performedmentioning
confidence: 99%